Kualitas Pelayanan Publik Dalam Pembuatan Paspor Di Kantor Imigrasi Kelas I Khusus TPI Batam - Seling Rahmawati; Timbul Dompak (SCIENTIA JOURNAL, 2022)
The Government as a provider of public service needed by the community must be responsible and continue to strive to provide the best service for the sake of improving public service. On the other hand, community satisfaction is measure of the success of public services provided by public service provided. This research is a descriptive study using a qualitative approach to determine the quality of public service in making passport at the Immigration Office Class I Special TPI Batam. The increasing number of passport application must of course be in line with improving the quality of service. The indicator used are tangible, reliability, responsiveness, assurance, emphaty, as well as factor that affect service quality namely organization, public service apparatus, service system. The result show that there are still indicators that have not been met, namely the tangible there is still a lack of parking space, the responsiveness of officer is still not responsive enough to provide direction, the emphaty is that there are officers who are not friendly in providing service, the assurance dimension is that there are still applicants who receive services exceeding the promised time, and the factor thataffects the service is the lack of human resources.